Latex Hypersensitivity among Allergic Egyptian Children: Relation to Parental/Self Reports - El-Sayed, Zeinab A.; El-Sayed, Shereen S.; Zaki, Rehab M.; Salama, Mervat A. (Pulmonary Medicine, 2014)
Background. Latex allergy is one of the major health concerns and allergic reactions to latex may be serious and fatal. Purpose. In this study, we sought to determine the frequency of latex hypersensitivity in a group of allergic Egyptian infants and children and its relation to the history provided by the patients or caregivers. Methods. We consecutively enrolled 400 patients with physician diagnosed allergic diseases. The study measurements included clinical evaluation for the site and duration of allergy, history suggestive of latex allergy, family history of allergy, and skin prick testing (SPT) using a commercial latex extract. Results. The study revealed that 16/400 (4%) patients had positive SPT; 11 of them only had positive history of sensitivity to latex. Positive latex SPT was reported in 3.4% (11/326) of patients with bronchial asthma, 5.9% (7/118) of patients with skin allergy, and 4.5% (2/44) of patients with allergic rhinitis. SPT was positive in 7.4% (4/54) of patients with concomitant respiratory and skin allergy. Latex SPT was more specific than sensitive (97.69% and 77.77%, resp.) with a negative predictive value of 99.47%. Conclusion. Although underrecognized, latex is an important allergen in the pediatric age group with a sensitization frequency of 4% among allergic children. It was observed to be especially associated with multiple allergic diseases coexisting in the same patient. Pediatric allergologists should educate their patients on latex allergy and encourage the use of latex-free products.